1989
DOI: 10.1051/limn/1989022
|View full text |Cite
|
Sign up to set email alerts
|

Bosminopsis brandorffi n.sp. (Crustacea, Cladocera) une nouvelle espèce de Bosminidae des systèmes Amazone et Orénoque

Abstract: Bosminopsis brandorffi, nouveau Bosminidae, se différencie de toutes les autres espèces du genre par l'importance de la région céphalique, l'absence de rostre, le grand développement de l'oeil et des antennules, la présence d'un fort talon abdominal. Mâles et femelles ephippiales sont inconnus. Bosminopsis brandorffi n.sp. (Crustacea, Cladocera), a new species of Bosminidae from the Amazon and Orinoco river systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Size. Length of females 0.30-0.41 mm in our material, 0.26-0.48 mm according to Rey, Vásquez [1989].…”
Section: Pressed (Figsmentioning
confidence: 61%
See 1 more Smart Citation
“…Size. Length of females 0.30-0.41 mm in our material, 0.26-0.48 mm according to Rey, Vásquez [1989].…”
Section: Pressed (Figsmentioning
confidence: 61%
“…At the same time, two species with strong morphological differences from B. deitersi were found in tropical South America, B. negrensis Brandorff, 1976and B. brandorffi Rey et Vásquez, 1989[Brandorff, 1976Rey, Vásquez, 1989]. They apparently do not belong to the deitersi-group and were placed into the genus Bosminopsis based on: (1) postabdomen narrowing distally, with a basal spine comparable to size with the postabdominal claw itself; (2) fused basal portions of the antennae I; (3) both exopod and endopod of the antenna I being three-segmented.…”
Section: Introductionmentioning
confidence: 98%
“…Ceriodaphnia cornuta also had higher densities in April and June/2008, being mostly present during the floodpeak period. Bosminopsis brandorffi Rey & Vásquez, 1989, Bosminopsis negrensis Brandorff, 1976 and M. rostrata also were recorded during the flood-peak period.…”
Section: Studies Of the Limnetic Zone Of Lakes In Other Regions Ofmentioning
confidence: 95%
“…Brandorff (1978) found that the most species-rich family in the Amazonian ecosystem was Bosminidae. Three Bosminidae species were observed, two of them endemic to the Amazon basin (Brandorff, 1976;Rey and Vásquez, 1989). Records of the genus Bosmina are common in many regions of Brazil, especially in reservoir environments (Paggi and José de Paggi, 1990;Lansac-Tôha et al, 2004;Perbiche-Neves and Nogueira, 2010).…”
Section: Composition Abundance Diversity and Richness Of Cladoceranmentioning
confidence: 98%
“…Indeed, Korinek (1984) directly stated that “ Bosminopsis deitersi was regarded as the only species within the genus”. However, in the last third of the 20th century, two species of Bosminopsis beyond the B. deitersi group were found in the Amazon River basin ( Brandorff, 1976 ; Rey & Vasquez, 1989 ).…”
Section: Introductionmentioning
confidence: 99%